Dipeptidyl peptidase-4 inhibitors attenuates osteoporosis in patients with diabetes: A nationwide, retrospective, matched-cohort study in Taiwan. Issue 7 (30th June 2022) - Chang, Chia-Hao; Lu, Chieh Hua; Chung, Chi-Hsiang; Su, Sheng-Chiang; Kuo, Feng-Chih; Liu, Jhih-Syuan; Li, Peng-Fei; Huang, Chia-Luen; Chen, Kuan-Chan; Ho, Li-Ju; Kuo, Chih-Chun; Chang, Chun-Yung; et al.
Abstract : Background: Patients with diabetes have a relatively high risk of fracture due to osteoporosis. However, the risk of osteoporosis associated with the use of oral hypoglycemic drugs and dipeptidyl peptidase-4 inhibitor (DPP-4i) by patients with diabetes is unclear. This study aimed to explore the effect of DPP-4i on the risk of osteoporosis in Taiwanese patients with type 2 diabetes mellitus (T2DM). Methods: This study enrolled 6339 patients on DPP-4i (DPP-4i group) and 25 356 patients without DPP-4i (non-DPP-4i group). They were matched by 1:4 propensity score matching, using confounding variables including sex, age, comorbidities, medication, and index year. Cox proportional hazards analysis was used to compare hospitalization and mortality during an average follow-up period of 7 years. Results: The mean age of patients in the two groups was 66 years. Men were slightly higher in number (51.79%) than women. At the end of the follow-up period, 113 (0.36%) patients had osteoporosis, of which 15 (0.24%) were in the case group and 98 (0.39%) in the control group. The risk of all-cause osteoporosis was significantly lower in the DPP-4i group than in the non-DPP-4i group (adjusted hazard ratio [HR] 0.616; 95% confidence interval [CI] 0.358–0.961; p = 0.011). Kaplan–Meier analysis showed that the preventive effect on osteoporosis was positively correlated with the cumulative dose of DPP-4i (log-rank, p = 0.039) with the class effect. Conclusion: Compared with not using DPP-4i, the use of DPP-4i in Taiwanese T2DM patients was associated with a lower risk of osteoporosis due to the class effect, and the preventive effect was dose-dependent. However, larger prospective studies are needed to validate this finding and to explore the possible mechanism of the preventive effect of DPP-4i.